Potensi Ekstrak Daun Bambu Apus (Gigantochloa apus Kurz)sebagai Bioherbisida Penghambat Perkecambahan Biji dan Pertumbuhan Gulma Rumput Grinting (Cynodon dactylon(L.) Pers) - Mukarlina, Nurhilda Frihantini, Riza Linda, (Universitas Tanjungpura, 2015)
Spring bamboo(GigantochloaapusKurz)leaves have allelochemicalcompounds such as phenol and flavonoidthat able to obstruct other plant growth, so that they have potentiality to be used as bioherbicide. The aim of this research war to coqnize the effective concentrations of spring bamboo leaves extract to obstruct seed germination and growth of devil’s grass (Cynodon dactylon (L.) Pers). The research was conducted for 7 months started from May to December 2014 in Biology Laboratory, Biology Greenhouse of Math and Science Faculty, and Forest products Tecnology Laboratory of Forestry Faculty of Tanjungpura University. The method of this research utilized the completely randomized design (CRD) with 5 treatments and 5replications. The concentrations of spring bamboo leaves extract used in this research were 0 g/ml, 0,17 g/ml, 0, 42 g/ml, 0,81 g/ml and 1,5 g/ml. The Result of this research shows that the administration of spring bamboo leaves extract can obstruct the seed germination and growt of devil’s grass. The lowest effectiveconcentration that can obstruct seed germination of devil’s grass is 0,81 g/ml. The lowest effective concentration that can obstruct the growt of devil’s grass is 0,17 g/ml.